ANALISIS STRATEGI GURU DALAM MENGATASI KESULITAN MEMBACA PERMULAAN SISWA KELAS II DI SD NEGERI PERIUK I - Eva Evitha, May; Fajar Nugroho, Oktian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by early reading difficulties found among second-grade students at SD Negeri Periuk I, Tangerang City. This study aims to analyze teacher strategies in overcoming early reading difficulties among students of class II B. A qualitative descriptive approach was employed with data collected through observation, interviews, and documentation. The findings reveal that teacher strategies encompass three main stages. First, the planning stage begins with individual mapping of students' reading abilities as the basis for determining appropriate strategies. Second, the implementation stage includes providing additional learning time, practicing vowel pronunciation, applying the syllable method, and utilizing learning media such as letter cards, picture books, and colored paper tailored to each student's needs. Third, the evaluation stage is conducted routinely through daily reading activities and fluency measurement. Consistent application of these strategies proved effective in improving students' early reading abilities while fostering their interest and confidence in reading.